PENGARUH KEPEMILIKAN KELUARGA TERHADAP KINERJA PERUSAHAAN: STRATEGI BISNIS SEBAGAI VARIABEL PEMODERASI (Studi pada Perusahaan yang Terdaftar di Bursa Efek Indonesia) - Alfi Nurbaiti (AKT 15 UMY 031, 2015)
*31 This research aims to test the influence of family ownership of a company's performance is measured using the return on equity (ROE) and business strategy as moderating variable. The subjects used in research are a public company listed on the Indonesia stock exchange in the period 2010-2013. The data used in this study come from secondary data. Data collection using the techniques of documentation. The results of the testing show that family ownership has no effect on the company's performance, but after plus business strategy as a family ownership moderating variable can affect the performance of the company. Where a good business strategy is could increase the influence of family ownership of the company's performance.